Hubungan Pola Asuh Terhadap Kejadian Stunting Pada Anak - Isnaini Karunia Lilla; Anik Enikmawati; Nurul Istiqomah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Stunting or short growth occurs when children do not receive the right kind of nutrition, especially in the womb and during the first two years of life. Children who are short, it means that their body growth and brain development has decreased and suffered permanent and irreversible damage. Children who experience stunting will have a greater risk of disease and death. The problem of nutritional deficiency is one of the most common problems in developing countries, such as Indonesia. To determine the relationship between parenting and the incidence of stunting in children. This study used a cross sectional design . The results showed that there was no relationship between parenting patterns and the incidence of stunting in children with a p-value of 0.150 > 0.5. The nutritional status of children, the majority of children have normal height with a total of 15 respondents (75%), 4 respondents (20%) have high height and 1 (5%) respondents have short height so that they are at risk of stunting, The level of parenting shows that parenting patterns are mostly in the high category of 17 respondents (85%) and there is no relationship between parenting patterns and the incidence of stunting in children.